Increased sensitization rates to tree pollens in allergic children and adolescents and a change in the pollen season in the metropolitan area of Seoul, Korea. Issue 5 (13th March 2021) - Lee, Kyung Suk; Kim, Kyunghoon; Choi, Young‐Jin; Yang, Seung; Kim, Chang‐Ryul; Moon, Jin‐Hwa; Kim, Kyu Rang; Lee, Yung‐Seop; Oh, Jae‐Won
Abstract: Introduction: Children with allergies are at greater risk of becoming sensitized to allergenic pollens in response to environmental changes. This study investigated the relationship between changes in pollination associated with meteorologic changes and the sensitization rates of children to tree pollen allergens in the metropolitan area of Seoul, Korea. Methods: The study population consisted of 8, 295 children who visited the pediatric allergy clinics at Hanyang University Seoul and Guri Hospital for allergy symptoms between January 1, 1998, and December 31, 2019. Pollen was collected at the two hospitals during the study using a Burkard 7‐day sampler. Meteorologic data were obtained from the National Weather Service. Results: Among the major tree pollens, the largest increase in allergic sensitization was to oak, hazel, and alder pollens (0.28% annually). The pollen‐sensitization rates increased annually within younger age groups. The duration of the pollen season was 98 days in 1998 and 140 days in 2019. Positive correlations were determined between the duration of the pollen season and the rates of sensitization to tree pollens, as well as between the pollen‐sensitization rates and increasing temperature. Conclusions: This study demonstrated the correlation between weather changes and the resulting changes in the pollen season with sensitization rates to allergenic pollens in children living in the Seoul metropolitan area. An annual increase in sensitization rates in younger children was determined. This pattern is expected to continue due to continuing climate change. Abstract :